The Concept of Morality According to Fazlur Rahman - Maria Ulfa; Ahmad Hisyam Syamil (Tasfiyah: Jurnal Pemikiran Islam, 2023)
This article examines the concept of morality according to Fazlur Rahman. Where serious morality problems make the younger generation of the Muslim community lose their true foundation of life. As a result, there will be suffering in life, loss of happiness and a meaningful life because of the secular and materialistic way of life that is permeated by their morality. This research will further develop morality, especially on how it can be applied in our education system, not only in rational and material aspects, but also includes moral and spiritual, with a comprehensive and integrative approach, under the tauhid worldview and paradigm, even morals must be applied in the age. Even morals must be applied in the age. This research is focused on the study of literature with a philosophical approach to analyzing Fazlur Rahman's books and books by other authors that are closely related to the topic. Thus, this study finds that Fazlur Rahman's concept of morality is a holistic view of the Qur'an on main themes, such as divinity, human action, nature, and eschatology. This view is the result of his original creation using the theory of multiple motions. From this point of view, Fazlur Rahman considers that the classical theologian's study of the Qur'an is a reductionist attitude, so it only leads to debate. In addition, through this theory, the problem of morality marginalizing humanity and divinity will be overcome. This study is one of the small contributions in order to re-articulate the general conclusions of Islamic metaphysics that have been built by Muslim intellectuals in the past according to the development of contemporary science.